What Determines Innovation in the Manufacturing Sector? Evidence from Pakistan. (The Pakistan Development Review, 2011)
This study analysed the behaviour of a sample of manufacturing firms in Pakistan in order to understand what determines innovative activity employing a panel data set for the years 2002 and 2006-07. Probit estimation results reveal that size of the firm and human resource quality are important internal factors that increase the likelihood of a firm innovating. Interestingly, whether a firm is exporting or not has no bearing. However, post innovating there is a large increase in number of firms who export. Externally, presence in a geographic cluster is important though further analysis reveals that the impact varies according to firm size. Size per se does not increase likelihood of innovating for medium sized firm who only have an advantage over small sized firms when present in a cluster. Large firms on the other hand continue to have an advantage and the advantage further increases with presence in a cluster. Finally, analysis by product and process innovators reveals that the characteristics of firms undertaking the two types of innovative activity are similar. The only noteworthy difference being that process innovation does not benefit from presence of a firm in a cluster which might be attributable to the more visible nature of product innovation which benefits from technological spillovers that are a characteristic of presence in a cluster. JEL classifications: O14, O31, O33, L6 Keywords: Innovation and Invention: Processes and Incentive, Developing Countries, Industry Study